Prosedur dan Teknis Diagnosa Kesulitan Belajar - Juwita Syahputri; Mirna Siti Herlisna Siregar; Rizqi Azzahro; Muhammad Risky Lubis; Atika Asna (Universitas Maritim AMNI Semarang, 2025)
Teachers are the most important component in the learning process in education. However, many students are not interested and bored during the learning process; some even fall asleep after being promised something. Students' ability to understand learning materials is influenced by various internal and environmental variables. Helping students in learning will have a negative impact on their development and quality of life in the future if not managed properly by parents and teachers. Therefore, parents, schools, and instructors all contribute to helping children overcome their challenges. Teachers have an important influence in the lives of their students. Thus, this diagnostic seeks to identify the root causes of students' learning challenges and identify solutions. This study aims to (1) identify factors that cause learning difficulties, (2) identify procedures and techniques for analyzing learning difficulties diagnosis, (3) determine the location of students' learning challenges or problems, and (4) help students who experience learning difficulties. Data collection was carried out using two techniques, namely observation of the teaching and learning process (PBM) and the student environment, as well as interviews with parents and instructors. According to the results of the study, students were less enthusiastic about learning because they were less interested and even tended to be lazy. Some students dislike some subjects because of their inability to understand certain elements. Therefore, such students rarely complete the assignments given and almost never take notes on certain lesson topics. Furthermore, the lack of interest in learning for some students can also be caused by their inability to understand the information that the instructor is trying to convey. This is caused by the failure of teachers to provide detailed examples of how to solve problems, and some teachers even fail to include examples when explaining the lesson content.